A Two-Year Review on Epidemiology and Clinical Characteristics of Dengue Deaths in Malaysia, 2013-2014. - Yuan Liang Woon; Chee Peng Hor; Narwani Hussin; Ariza Zakaria; Pik Pin Goh; Wee Kooi Cheah (Public Library of Science (PLoS), 2016)
Dengue infection is the fastest spreading mosquito-borne viral disease, which affects people living in the tropical and subtropical countries. Malaysia had large dengue outbreaks in recent years. We aimed to study the demographics and clinical characteristics associated with dengue deaths in Malaysia.We conducted a retrospective review on all dengue deaths that occurred nationwide between 1st January 2013 and 31st December 2014. Relevant data were extracted from mortality review reports and investigational forms. These cases were categorized into children (<15 years), adults (15-59 years) and elderly (≥60 years) to compare their clinical characteristics.A total of 322 dengue deaths were reviewed. Their mean age was 40.7±19.30 years, half were females and 72.5% were adults. The median durations of first medical contact, and hospitalization were 1 and 3 days, respectively. Diabetes and hypertension were common co-morbidities among adults and elderly. The most common warning signs reported were lethargy and vomiting, with lethargy (p = 0.038) being more common in children, while abdominal pain was observed more often in the adults (p = 0.040). But 22.4% did not have any warning signs. Only 34% were suspected of dengue illness at their initial presentation. More adults developed severe plasma leakage (p = 0.018). More than half (54%) suffered from multi-organ involvement, and 20.2% were free from any organ involvement. Dengue deaths occurred at the median of 3 days post-admission. Dengue shock syndrome (DSS) contributed to more than 70% of dengue deaths, followed by severe organ involvement (69%) and severe bleeding (29.7%).In Malaysia, dengue deaths occurred primarily in adult patients. DSS was the leading cause of death, regardless of age groups. The atypical presentation and dynamic progression of severe dengue in this cohort prompts early recognition and aggressive intervention to prevent deaths.National Medical Research Registry (NMRR, NMRR-14-1374-23352).